Penerapan Metode Multiplicative Decomposition dan Autoregressive Integrated Moving Average dalam Prediksi Penjualan Produk Manufaktur pada PT. XYZ - Melvin Soeharto; Silvia Rostianingsih; Leo Willyanto Santoso (Universitas Kristen Petra, 2022)
PT. XYZ is a company engaged in the manufacture of drinking water (AMDK). PT. XYZ conducts product sales transactions in large quantities every day, so the large number of existing sales transactions will certainly affect the daily necessities inventory in the company. The problem that occurs in the company is regarding overstock and understock. Based on the problems that occur, the researchers will apply the Multiplicative Decomposition and Autoregressive Integrated Moving Average (ARIMA) methods to process a large number of sales-data which is used as information. So, the purpose of this study is to implement the Multiplicative Decomposition and Autoregressive Integrated Moving Average (ARIMA) methods to predict sales of mineral water goods at PT. XYZ. The test system will use the Mean Absolute Percentage Error (MAPE) method.